Asuhan Kebidanan Pada Ibu Bersalin Normal Di PMB Nikma.Z, SST Wilayah Kerja Puskesmas Air Tiris Tahun 2024 - Adelia, Annisa; Syahda, Syukrianti (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Normal Childbirth is delivery with a posterior presentation of the fetus that occurs spontaneously with a labor duration within normal limits, low risk from the beginning of labor until parturition with a gestation period of 37-42 weeks. The aim of this research is to provide normal delivery care to mothers giving birth at PMB Nikma. Z, SST Air Tiris Health Center Working Area on June 14 2024. Case Study Research Results given to Ny.D, by monitoring from stage I to stage IV, the mother said she was feeling sick, a little worried. Midwifery care is provided in the form of teaching correct breathing techniques, pushing techniques and telling the mother the best position to facilitate opening. Based on the midwifery care provided to Ny.D P3A0H3 40 weeks gravid results showed that the mother and baby were in good condition, with vital signs examination results within normal limits, good uterine contractions and no post partum bleeding. It can be concluded that the care provided was carried out well and obtained positive results. It is hoped that midwives and institutions will use this research as a reference or material to broaden their knowledge and develop knowledge about midwifery care for women giving birth normally according to evidence based.